2021
DOI: 10.1038/s41598-020-80626-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function analysis of TOPBP1’s role in ATR signaling using the DSB-mediated ATR activation in Xenopus egg extracts (DMAX) system

Abstract: The protein kinase ATR is activated at sites of DNA double-strand breaks where it plays important roles in promoting DNA end resection and regulating cell cycle progression. TOPBP1 is a multi BRCT repeat containing protein that activates ATR at DSBs. Here we have developed an experimental tool, the DMAX system, to study the biochemical mechanism for TOPBP1-mediated ATR signalling. DMAX combines simple, linear dsDNA molecules with Xenopus egg extracts and results in a physiologically relevant, DSB-induced activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…ATR signaling requires one of two known activators, either TOPBP1 or ETAA1 [ 7 ]. Recent work from our group has shown that, in Xenopus egg extracts (XEEs), TOPBP1 is solely responsible for ATR activation at DSBs [ 8 , 9 ]. TOPBP1 is a multi-functional protein with roles in ATR signaling, the initiation of DNA replication, transcriptional regulation, and DNA repair during mitosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…ATR signaling requires one of two known activators, either TOPBP1 or ETAA1 [ 7 ]. Recent work from our group has shown that, in Xenopus egg extracts (XEEs), TOPBP1 is solely responsible for ATR activation at DSBs [ 8 , 9 ]. TOPBP1 is a multi-functional protein with roles in ATR signaling, the initiation of DNA replication, transcriptional regulation, and DNA repair during mitosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…To study this important problem we utilized our recently developed DMAX system, which is based on XEEs and the use of linear dsDNA templates [ 8 , 9 ]. For DMAX, we use the high-speed supernatant (HSS) form of XEE, where traditionally prepared crude extracts are centrifuged at high speed to produce an extract containing just soluble protein, and devoid of pigment granules, yolk platelets, and membranes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations